Lipopeptide biosurfactant pseudofactin II induced apoptosis of melanoma A 375 cells by specific interaction with the plasma membrane. - Tomasz Janek (Public Library of Science (PLoS), 2013)
In the case of melanoma, advances in therapies are slow, which raises the need to evaluate new therapeutic strategies and natural products with potential cancer cell inhibiting effect. Pseudofactin II (PFII), a novel cyclic lipopeptide biosurfactant has been isolated from the Arctic strain of Pseudomonas fluorescens BD5. The aim of this study was to investigate the effect of PFII on A375 melanoma cells compared with the effect of PFII on Normal Human Dermis Fibroblast (NHDF) cells and elucidate the underlying mechanism of PFII cytotoxic activity. Melanoma A375 cells and NHDF cells were exposed to PFII or staurosporine and apoptotic death was assessed by monitoring caspase 3-like activity and DNA fragmentation. From time-dependent monitoring of lactate dehydrogenase (LDH) release, Ca(2+) influx, and a correlation between Critical Micelle Concentration (CMC) we concluded that cell death is the consequence of plasma membrane permeabilisation by micelles. This finding suggests that pro-apoptotic mechanism of PFII is different from previously described cyclic lipopeptides. The mechanism of PFII specificity towards malignant cells remains to be discovered. The results of this study show that PFII could be a new promising anti-melanoma agent.